2017
DOI: 10.1186/s12872-017-0483-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of serum cystatin C and glomerular filtration rate with vascular lesions and severity in acute coronary syndrome

Abstract: BackgroundThe aim of this study was to evaluate the predictive value of cystatin C (CysC) and estimated glomerular filtration rate (eGFR) regarding vascular lesions and their severity in patients with acute coronary syndrome (ACS).MethodsAccording to the results of coronary angiography, 195 ACS patients were divided into a single-vascular-lesion group (91 cases), a dual-vascular-lesion group (67 cases), and a multiple-vascular-lesion group (37 cases) to assess the severity of coronary artery disease according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Unlike SCr, urinary IgG, or transferrin, Cys-C is not influenced by gender, race, and muscle mass, and thus has recently drawn considerable attention (Peralta et al, 2011). Cys-C also exhibits predictive value for the prognosis of renal and cardiovascular diseases (Peralta et al, 2011;Ozkok et al, 2014;Barr et al, 2017;Zhang et al, 2017). In our study, we found that STS plus ARBs therapy was better than ARBs alone in improving urinary protein, SCr, and eGFR, which also suggested that STS could be beneficial as an "add-on" medication for hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike SCr, urinary IgG, or transferrin, Cys-C is not influenced by gender, race, and muscle mass, and thus has recently drawn considerable attention (Peralta et al, 2011). Cys-C also exhibits predictive value for the prognosis of renal and cardiovascular diseases (Peralta et al, 2011;Ozkok et al, 2014;Barr et al, 2017;Zhang et al, 2017). In our study, we found that STS plus ARBs therapy was better than ARBs alone in improving urinary protein, SCr, and eGFR, which also suggested that STS could be beneficial as an "add-on" medication for hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pascual et al suggested that cystatin C independently predicts death or heart failure rehospitalization with greater accuracy than creatinine [ 22 ]. Various studies found that cystatin C is also an important prognostic factor of a poor outcome in patients with acute coronary syndrome [ 23 , 24 ]. These all demonstrated the prognostic significance of cystatin C in cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of serum Cys C was measured using a kit provided by Kyokuto Pharmaceutical Industrial (Tokyo, Japan), and the level is expressed in units of mg/dL. 13 The reference value of Cys C is ≤1.0 mg/L. In all patients, the serum Cys C concentration was measured within 24 h after admission.…”
Section: Methodsmentioning
confidence: 99%